Chronic ethanol diet increases regulatory T‐cell activity and inhibits hepatitis C virus core‐specific cellular immune responses in mice. Issue 7 (4th July 2013) - Ortiz, Vivian; Wands, Jack R.
<x xml:space="preserve">Abstract</x> Aim Chronic ethanol consumption is associated with persistent hepatitis C viral (HCV) infection. This study explores the role of the host cellular immune response to HCV core protein in a murine model and how chronic ethanol consumption alters T‐cell regulatory (Treg) populations. Methods BALB/c mice were fed an isocaloric control or ethanol liquid diet. Dendritic cells (DC) were isolated after expansion with a hFl3tL‐expression plasmid and subsequently transfected with HCV core protein. Core‐containing DC (1 × 106) were s.c. injected (×3) in mice every 2 weeks. Splenocytes from immunized mice were isolated and stimulated with HCV core protein to measure generation of viral antigen‐specific Treg, as well as secretion of interleukin (IL)‐2, tumor necrosis factor (TNF)‐α and IL‐4. Cytotoxicity was measured by lactate dehydrogenase release from HCV core‐expressing syngeneic SP2/19 myeloma cells. Results Splenocytes from mice immunized with ethanol‐derived and HCV core‐loaded DC exhibited significantly lower in vitro cytotoxicity compared to mice immunized with HCV core‐loaded DC derived from isocaloric pair‐fed controls. Stimulation with HCV core protein triggered higher IL‐2, TNF‐α and IL‐4 release in splenocytes following immunization with core‐loaded DC derived from controls as compared to chronic ethanol‐fed mice. Splenocytes derived from mice immunized with core‐loaded DC isolated from ethanol‐fed mice exhibited a significantly higher CD25+FOXP3+ and CD4+FOXP3+Treg population. Conclusion These results suggest that immunization with HCV core‐containing DC from ethanol‐fed mice induces an increase in the CD25+FOXP3+ and CD4+FOXP3+Treg population and may suppress HCV core‐specific CD4+ and CD8+ T‐cell immune responses.